2016
DOI: 10.1002/pen.24433
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electrical conductivity and other related properties of epoxidized natural rubber/carbon nanotube composites by optimizing concentration of 3‐aminopropyltriethoxy silane

Abstract: Carbon nanotube (CNT)-filled epoxidized natural rubber (ENR) composites were prepared by mixing in an internal mixer and thereafter on a two-roll mill. Silane coupling agent, namely 3-aminopropyltriethoxy silane (APTES), was directly incorporated in the ENR-CNT composites during mixing of rubber and CNTs in the mixer, to perform in situ functionalization. It was found that pre-crosslinking of ENR and APTES occurred especially at high APTES concentrations, such as 0.06 mL/(g of CNTs) and caused strong CNT agglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Such observations indicated that the addition of MWCNTs improved the stiffness of the nanocomposites. Tensile properties of ENR-CNT composites prepared by in situ functionalization with various APTES silane concentrations were investigated [ 40 ]. Figure 4 shows stress-strain curves of ENR vulcanizate and ENR-CNT composites without and with APTES at concentrations from 0.06 to 0.01 mL/(g of CNTs).…”
Section: Mechanical Properties Of Rubber Nanocomposites Of Carbon mentioning
confidence: 99%
See 1 more Smart Citation
“…Such observations indicated that the addition of MWCNTs improved the stiffness of the nanocomposites. Tensile properties of ENR-CNT composites prepared by in situ functionalization with various APTES silane concentrations were investigated [ 40 ]. Figure 4 shows stress-strain curves of ENR vulcanizate and ENR-CNT composites without and with APTES at concentrations from 0.06 to 0.01 mL/(g of CNTs).…”
Section: Mechanical Properties Of Rubber Nanocomposites Of Carbon mentioning
confidence: 99%
“…In view of this, these carbon containing fillers has been receiving considerable amount of attention as filers in rubber nanocomposites due to their superior properties. When considering all these aspects, the present article reviews mechanical properties, dynamical mechanical properties, Payne, and Mullin effects of NR, SBR, NBR, EPDM, and EVA rubbers filled with graphitic fillers anticipating their superior applications in multifaceted fields [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 …”
Section: Introductionmentioning
confidence: 99%
“…Such observation indicated that the addition of MWCNTs improved the stiffness of the nanocomposites. Tensile properties of ENR-CNT composites prepared by in situ functionalization with various APTES silane concentrations were investigated [40]. Figure 4 show stress-strain curves of ENR vulcanizate and ENR-CNT composites without and with APTES at concentrations from 0.06 to 0.01 mL/(g of CNTs).…”
Section: Mechanical Properties Of Carbon Filler Incorporated Nr and Imentioning
confidence: 99%
“…Stress-strain curves of ENR vulcanizate and ENR-CNT composites without and with APTES at concentrations from 0.06 to 0.01 mL/ (g of CNTs). Reproduced with permission from Wiley[40].…”
mentioning
confidence: 99%
“…Several organosilanes have been developed and evaluated over the years . The most widely used silane coupling agent for tire applications is bis ‐(triethoxysilylpropyl) tetrasulfide (TESPT) which has been reported to provide not only a good coupling efficiency, but also additional crosslinks in the rubber vulcanizates .…”
Section: Introductionmentioning
confidence: 99%